„Licencja do nauczania” czyli 'Lehrbefugnis' i 'Lehrbefähigung' w tłumaczeniu maszynowym - Mikołajczyk, Beata; Waliszewska, Karolina; Aptacy, Jarosław (2022)
The subject of this article is the machine translation (MT) of the German terms Lehrbefugnis (“authorisation to teach”) and Lehrbefähigung (“teaching qualification”) into Polish. First, the role of these terms in international academic careers is highlighted and then their semantics is described. The next point of the article is basic information about the principles of MT. The structural equivalents of German terms in Polish and typical mistakes made by translators are also discussed. The concluded part of the analysis is that translators are not yet able to translate such specific terms correctly, therefore further work (also of a linguistic nature) is necessary to improve their quality, e.g. by supplementing lexical resources.
Keywords: machine translations; specialist terminology; German and Polish law on science and higher education; scientific advancement; principles of habilitation